2020
DOI: 10.1002/glia.23785
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the transcriptional fingerprint of satellite glial cells following peripheral nerve injury

Abstract: Satellite glial cells (SGCs) are homeostatic cells enveloping the somata of peripheral sensory and autonomic neurons. A wide variety of neuronal stressors trigger activation of SGCs, contributing to, for example, neuropathic pain through modulation of neuronal activity. However, compared to neurons and other glial cells of the nervous system, SGCs have received modest scientific attention and very little is known about SGC biology, possibly due to the experimental challenges associated with studying them in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(125 citation statements)
references
References 129 publications
(204 reference statements)
12
101
0
Order By: Relevance
“…This analysis also indicated that the cell cycle term was enriched in macrophages, and downregulated in SGC ( Supplementary Fig. 3a, Supplementary Data 4), supporting the recent finding that macrophages but not SGC undergo cell cycle after nerve injury 38 .…”
Section: Sgc Upregulate Lipid Metabolism In Response To Nerve Injurysupporting
confidence: 86%
See 3 more Smart Citations
“…This analysis also indicated that the cell cycle term was enriched in macrophages, and downregulated in SGC ( Supplementary Fig. 3a, Supplementary Data 4), supporting the recent finding that macrophages but not SGC undergo cell cycle after nerve injury 38 .…”
Section: Sgc Upregulate Lipid Metabolism In Response To Nerve Injurysupporting
confidence: 86%
“…1d). Whereas glutamine synthetase (Glul/GS) has been used as a SGC specific marker at the protein level 38,39 , our analysis showed a nonspecific expression in almost all cells in the DRG ( Fig. 1f and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Sensory neurons are found within the DRG, which is composed of many different cell types, including Schwann cells and satellite glial cells. These cells are known to contribute to acute and chronic pain states (Goncalves et al, 2018;Lemes et al, 2018;Jager et al, 2020) but how they interact with sensory neurons is poorly understood. Moreover, how sensory neurons may interact with these cells through release of transmitter substances is almost completely unexplored.…”
Section: Figure 2 Cell Type Gene Enrichment Analysis Reveals Specificmentioning
confidence: 99%